Rapid Diagnosis of Invasive Aspergillosis and Active Hepatitis-B Virus Co-Infection in a HIV-1 Infected Patient Using Cell Free DNA Sequencing. (27th November 2020) - Roy, Moni; Kim, Joseph Y.; Lin, Rone-Chun
Multiple simultaneous opportunistic infections in Human Immunodeficiency virus-1/Acquired immunodeficiency syndrome (HIV-1/AIDS) is a known and dreaded occurrence that often leads to poor outcomes. We present a case of disseminated aspergillosis and active Hepatitis-B virus (HBV) infection in such a host, where cell free DNA (cfDNA) next generation sequencing (NGS) of plasma was used to expedite diagnosis. Bronchoscopy was avoided and treatment was started expeditiously. In this case report we discuss the interpretation of the cfDNA NGS, and its potential role for early diagnosis and avoidance of invasive testing.